POSSIBILITIES OF LEARNING AUTOCAD 2013 FOR GRAMMAR SCHOOLS - Milan, KLEMENT; KUBRICKY, Jan (Trends in education, 2014)
Teaching technically oriented graphics systems is a relatively new, unexplored area within the framework of general secondary schools. In order to compile, properly design, and implement the teaching of the basics of creating technical drawings using AutoCAD system, it is necessary to properly structure and adapt the existing approaches to teaching computer science oriented subjects at these schools. In the context of the above mentioned, it seems particularly suitable to make use of interdisciplinary relations, which enable the application of the theoretical knowledge acquired in mathematics, chemistry, and physics on solving application and visualization tasks using computer aided drawing and modelling.For these reasons, a joint project of six grammar schools of the Olomouc Region and the Department of Technical and Information Education was implemented, aimed at the introduction of the subject "Application of mathematics and chemistry using computer technical drawing ". It was divided into 10 teaching units . The thematic unit, the design and the content of which are presented by the submitted paper, is focused on the practical application of the theoretical knowledge students gained in mathematics and chemistry lessons in the field of computer aided engineering drawing.
Keywords: concept of teaching; computer-aided technical drawing; Autodesk AutoCAD; teaching module.